PKP-012 Monitoring of vancomycin in 62 patients with central nervous system infections. (24th March 2015) - Franco, F; Viguera-Guerra, I; Aumente, MD
Abstract : Background: Since the release of linezolid vancomycin has been downgraded as an alternative in the treatment of central nervous system (CNS) infections caused by Gram-positive bacteria on account of its bad penetration and high incidence of nephrotoxicity. There are no studies with enough patients to support this trend. Purpose: To evaluate the efficacy and safety of vancomycin in CNS infections, and the impact of monitoring its pharmacokinetics. Material and methods: Descriptive retrospective study which included all patients with CNS infections treated with vancomycin and monitored. Patients aged under 18 and those who received less than 5 days' treatment with vancomycin were excluded. Results: A total of 62 patients were included, 39 with previous surgical intervention (SI) in the CNS. The most common diagnoses in the group with prior SI were bacterial meningitis (51%), fistula of cerebrospinal fluid (CSF) (21%) and shunt infection (21%). All had baseline neurological disease – neoplasms (46.2%) and subarachnoid haemorrhage (25.6%). Most patients without prior SI (n = 23) were diagnosed with bacterial meningitis (n = 21) and just 2 with a brain abscess. The infective pathogen was isolated in 39 samples of CSF. All isolated microorganisms were sensitive to vancomycin. 63.7% of the isolated microorganisms were coagulase-negative Staphylococcus, with a MIC = 2 in 23.7%. The initial and adjusted mean doses of vancomycin were 35.6 ± 9.3 mg/kg/day and 39.9 ± 15.2 mg/kg/day respectively. The median initial and adjusted Cmin were 10.04 (6.16) mcg/ml and 14.67 (3.66) mcg/ml respectively. Laboratory-confirmed CSF clearance was obtained in 26 of the 39 isolates, 73.1% during the first 10 days of treatment. The overall mortality was 5.8%, but only one death was related to the CNS infection. Although Cmin above 20 mcg/ml was recorded in 15 patients, none developed nephrotoxicity. Conclusion: Vancomycin is still an agent of choice for CNS infections. Vancomycin trough concentrations of 15–20 mcg/ml are recommended to achieve clinical effectiveness for CNS infections without causing nephrotoxicity. References and/or acknowledgements: No conflict of interest.